Mucosal cell responses to Clostridium difficile toxins - Mullan, Nivette K. (2011)
Colonic inflammation in C. difficile infection is mediated by released toxins A and B. I have investigated responses to C. difficile toxin A and B by primary human colonic myofibroblasts, which represent a distinct subpopulation of mucosal cells that are normally located below the intestinal epithelium and epithelial cell lines, Caco-2 and HT29. Myofibroblasts, isolated from normal human colonic mucosal specimens, Caco-2 and HT29 cells incubated with purified toxin A or B displayed a dose dependent response. Myofibroblast morphology changed to a stellate shaped cell, with processes that were immunoreactive for alpha smooth muscle actin. Most of the myofibroblasts remained viable, with persistent stellate morphology, despite exposure to high concentrations (up to 10 μ g/ml) of toxin A for 72 h. In contrast, a majority of the toxin B exposed myofibroblasts lost their processes prior to cell death over 24-72 h. Investigating toxin A+B on myofibroblasts, at low concentrations, toxin A provided protection against toxin B-induced cell death. Most of the intestinal epithelial, HT29 cells remained viable despite exposure to high concentrations of either toxin (up to 10 μ g/mi). By contrast, a significant loss in cell viability was observed in Caco-2 cells exposed to either toxin. Within 4 h, myofibroblast and epithelial cell types exposed to either toxin A or B lost expression of the non-glucosylated form of Racl, but total intracellular RhoA remained unchanged in myofibroblasts and Caco-2 cells. A time-dependent reduction in RhoA expression was seen in HT29 in response to toxin A or B. Active RhoA expression was lost within 4h in myofibroblasts exposed to either toxin. Despite pre-exposure to high concentrations of toxin A for 3 h, colonic myofibroblasts were able to recover their morphology and proliferative capacity during prolonged culture in medium. This was also shown when pre-exposure to toxin A was extended to 48 h. However, toxin B-pre-exposed myofibroblasts were not able to recover. In conclusion, primary human colonic mucosal myofibroblasts are resistant to toxin A (but not toxin B)-induced cell death. Responses by colonic myoflbroblasts may play an important role in mucosal protection, repair, and regeneration in colitis due to C. difficile infection. Investigation into the apparent resilience of HT29 cells has highlighted the importance of cell specific substrate specificity by C. difficile toxins.